Pengembangan Agrowisata Berbasis Wisata Edukasi Di Mini Agrowisata DKPP Surabaya - Fitriani, Selvi Dwi; Larasati, Deviona Ayu; Dewi, Amalia Dinda Candra; Alawi, A. Muammar (JURNAL DESTINASI PARIWISATA, 2024)
Agrotourism is a tourism development activity related to agriculture or rural activities aimed at increasing the added value of village welfare and agricultural activities themselves that can be interspersed with educational activities. This research aims to determine the development carried out by Mini Agrotourism DKPP Surabaya. With the development of education through agrotourism, it is hoped that education can be an attraction to attract tourists to visit. In addition, it can improve the economy of the surrounding community. This research uses a qualitative descriptive method. The data collection technique used is through research and literature analysis in journals, websites, and theses. The results of the study indicate that Mini Agrotourism DKPP Surabaya uses the concept of urban agriculture, namely hydroponics, due to land limitations. Mini Agrotourism DKPP Surabaya develops its tourism as educational tourism and as a learning facility for agriculture, plantations, and animal husbandry for children and students. The conclusion of this study is that Mini Agrotourism DKPP Surabaya has succeeded in developing agrotourism based on educational tourism, but further developments are needed to maintain this success. This education-based agrotourism provides positive benefits for children and students in Surabaya because they gain knowledge about agriculture, plantations, and even animal husbandry, which are rarely found in urban areas. Keywords: Development, agrotourism, educational tourism